ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL SPLDV MENGGUNAKAN KERANGKA NEWMAN - Syihab Zamzami, Ahmad; Nandang Mustafa, Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning on the topic of Systems of Linear Equations in Two Variables (SLETV) still reveals various student difficulties, particularly in solving word problems. Students frequently make errors in understanding problems, constructing mathematical models, and carrying out solution procedures. This study aimed to analyze the types of students’ errors in solving SLETV word problems based on Newman’s Error Analysis procedure. The research employed a qualitative descriptive approach involving eighth-grade students of SMP Negeri 15 Kota Serang selected through purposive sampling. Data were collected through written tests, semi-structured interviews, observations, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldaña model, while data validity was ensured through triangulation techniques. The results showed that students experienced errors at each stage of Newman’s procedure, including reading, comprehension, transformation, process skills, and encoding errors. The most dominant errors occurred at the transformation stage, particularly in translating word problems into mathematical models of SLETV. This study concludes that students’ errors in solving SLETV word problems are complex and multilayered. Therefore, systematic and continuous instructional improvements are needed, such as the use of contextual problems and problem-based learning approaches, to help students become more familiar with real-life situations and develop more meaningful problem-solving skills.